Nanopore sequencing analysis of integron gene cassettes in sewages and soils - An, Xin-Li (2023)
Integrons are genetic elements that can facilitate rapid spread of antibiotic resistance by insertion and removal of genes. However, knowledge about the diversity and distribution of gene cassettes embedded in class 1 integron is still limited. In this study, we sequenced integron gene cassettes using nanopore sequencing and quantified antibiotic resistance genes (ARGs) and integrase genes in the manured soils and sewages of a bioreactor. The results showed that class 1 integron integrase genes were the most abundant in soils and sewages compared with class 2 and class 3 integrase genes. Long-term manure application exacerbated the enrichment of total ARGs, integrase genes and antibiotic resistance-associated gene cassettes, while antibiotics and heavy metals showed no impact on the overall resistome profile. Sewage treatment could efficiently remove the absolute abundance of integrase genes (~3 orders of magnitude, copies/L) and antibiotic resistance gene cassettes. The resistance gene cassettes mainly carried the ARGs conferring resistance to aminoglycoside and beta-lactams in soils and sewages, some of which were persistent during the sewage treatment. This study underlined that soil and sewage were potential reservoirs for integron-mediated ARGs transfer, indicating that anthropogenic activity played a vital role in the prevalence and diversity of resistance gene cassettes in integrons.